Optimizing Catfish Marketing in Forest Communities of Ido Municipality (The Impact of Seasonality Storage and Pricing on Performance) - Adebayo Samson Adeoye (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2024)
The challenges catfish marketers encounter due to the seasonality of catfish production in most rural areas have masterminded difficulty in free product distribution to consumers, which invariably hampers their income. Therefore, the study examined catfish marketing in Oyo state, Nigeria. A multistage sampling technique was adopted to select sampled respondents. First, five wards were selected purposively out of 10 in the study area. Next, 10 markets were randomly selected evenly from each ward. Finally, 120 marketers were selected from each of the sampled markets. The questionnaire was adopted for data collection on the demographic characteristics of respondents, marketing channels available, gross margin estimation of catfish marketing, factors influencing catfish marketing, and constraints on catfish marketing. Data was analyzed using frequencies, percentages, mean scores, gross margin, linear regression, and benefit-cost ratio (BCR). Key findings indicate that 74% of respondents earn between ₦200,000 and ₦400,000 ($476 - $952) monthly, with a gross margin of 64.4%, meaning marketers retain $0.644 for every revenue. The analysis showed that the identified influencing factors could explain 58% of variations in catfish marketing. The benefit-cost ratio (BCR) was found to be 1.41:1, indicating a positive return on investment, with marketers retaining approximately ₦1,453,056 from their activities. However, constraints such as seasonality, high transportation costs, and inadequate cold storage facilities were significant hurdles. Therefore, establishing commodity markets in rural areas to enhance connections between fish farmers and buyers, promoting stakeholder partnerships, and providing training on product quality and storage were recommended. These measures aim to improve the efficiency and profitability of catfish marketing.